Advances in Multimedia Information Processing - PCM 2010 11th Pacific Rim Conference on Multimedia, Shanghai, China, September 2010, Proceedings, Part II - Qiu, Guoping; Lam, Kin Man; Kiya, Hitoshi; Xue, Xiang-Yang; Kuo, C.-C. Jay; Lew, Michael S. (Springer eBooks., 2011)
This book constitutes the proceedings of the 11th Pacific Rim Conference on Advances in Multimedia Information Processing, held in Shanghai in September 2010.